The Financial Literacy and Fintech Technology On Financial Management Of Students at Makassar State University - Sahabuddin, Romansyah; Arif, Hery Maulana; Azilah, A.Nur; Nengsih, Nur Suka; Amsa, Reni (International Humanity Advance, Business & Sciences, 2024)
Financial management is important for students who often face financial challenges due to fluctuating income and expenses. The purpose of this study was to determine the impact of financial education and utilization of financial technology (fintech) on the financial management practices of Makassar State University students. The study used a survey method and 250 students were selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression to assess the effect of financial knowledge and the use of financial technology on financial management. The results showed that financial education and financial technology utilization have a significant impact on students' financial management, and financial technology has a greater impact. This study highlights the importance of strong financial literacy and effective use of financial technology to improve students' financial management skills. It is recommended that universities strengthen educational programs that focus on financial knowledge and financial technology so that students are better able to face future financial challenges.